تقدير الذات وعلاقته بالتكيف الاجتماعي لدى تلاميذ السنة أولى ثانوي دراسة ميدانية بثانوية المجاهد زابي صالح بلدية الخبانة- بوسعادة - إكرام نصري; عائشة حليب; نعيمة برابح (جامعة محمد بوضياف -المسيلة, 2025)
هدفت هذه الدراسة إلي التعرف على العلاقة بين تقدير الذات والتكيف الاجتماعي لدى تلاميذ السنة أولى ثانوي، وتم استخدام المنهج الوصفي والذي من خلاله حاولنا معرفة العلاقة بين تقدير الذات والتكيف الاجتماعي حيث بلغت عينة الدراسة 60 تلميذ وتلميذة متمدرسين بالنسبة للسنة أولى ثانوي يتراوح سنهم ما بين (¬15 سنة -18 سنة)، وقد تم اختيارهم بطريقة عشوائية، وشكلوا ما نسبته 47% من مجتمع الدراسة الأصلي، ولتحقيق أهداف الدراسة تم استخدام مقياس تقدير الذات لصاحبته "سايح زليخة" (2014)، ومقياس التكيف الاجتماعي لمحمود عطية هنا. وتم الاعتماد على نظام SPSS للتحليل الإحصائي لنتائج الدراسة، وكانت النتائج التي تم التوصل إليها: - وجود علاقة بين تقدير الذات ودرجة التكيف الاجتماعي. - مستوى تقدير الذات عند أفراد العينة جاء معتدلا. - مستوي التكيف الاجتماعي جاء معتدلا لدى عينة الدراسة. - وجود فروف دالة إحصائيا على مقياس تقدير الذات لصالح الذكور مما يدل على أن الذكور الأكثر اتساما بتقدير الذات من الإناث. - وجود فروق دالة إحصائيا على مقياس التكيف الاجتماعي لصالح الإناث مما يدل على أن الإناث الأكثر اتساما بالتكيف الاجتماعي من الذكور. الكلمات المفتاحية: التكيف الاجتماعي، تقدير الذات، أولى ثانوي، تلاميذ. Summary: This studyaimed to identify the relationshipbetween self-esteem and social adaptation among first-yearsecondaryschoolstudents. The descriptive approachwasused, throughwhichwetried to find out the relationshipbetween self-esteem and social adaptation. The studysampleconsisted of 60 male and femalestudentsstudying for the first year of secondaryschool, whoseagesrangedbetween( ¬15 years - 18 years), and theywereselectedrandomly, and theyconstituted 47% of the original study population. To achieve the objectives of the study, the self-esteemscale by SayehZulekha (2014) and the social adaptation scale by Mahmoud Attiawereusedhere. The SPSS system wasreliedupon to statisticallyanalyze the results of the study, and the resultsreachedwere: - There is a relationshipbetween self-esteem and the degree of social adaptation. The level of self-esteemamong the samplememberswasmoderate. The level of social adaptation wasmoderateamong the studysample. - There are statisticallysignificantdifferences on the self-esteemscale in favor of males, whichindicatesthat males are more characterized by self-esteemthanfemales. - There are statisticallysignificantdifferences on the social adaptation scale in favor of females, whichindicatesthatfemales are more socially adaptive than males. Keywords: social adaptation, self-esteem, first secondaryschool, students..